Transaction in non-cash payments through Ovo application: an Islamic judgment study by the Mazhab Syafi'i - Ahmad Arif Zulfikar; Pidayan Sasnifa (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam, 2020)
Along with the development of technology, nowadays payment can be done through smart phones with applications, those application enable transactions to pay for goods or services only through websites, credit cards or similar. OVO is one of smartphone applications available. The purpose of this article is to analyze OVO-related services in online transportation payments based on the perspective of shafi'i fiqh. The research method used is normative law, the specification of this study is descriptive analysis which is in the form of detailed and measurable exposure analyzed with an applicable legal norm, while data analysis techniques used is content analysis. The results show that based on the perspective of Ulema 'Syafi'iyah in terms of objectives and OVO application transactions, the contract used was a wadi'ah contract, but the OVO application according to the wadi'ah category of the user category in fiqh science was invalid because the user could not take money or balance on the application, while in theory the balance or money is should be the user's full ownership.